Formulation and evaluation of mucoadhesive microspheres of metronidazole - Chechare, Dheeraj D.; Siddaiah, M. (Journal of Applied Pharmaceutical Research, 2024)
Objective: Develop and evaluate mucoadhesive microspheres using Chitosan, Sodium alginate, and Sodium carboxymethyl cellulose (NaCMC) for sustained oral delivery of Metronidazole, aiming to improve bioavailability. Methods: Metronidazole-loaded microspheres were prepared via ionotropic gelation method with varying polymer ratios. Particle size, entrapment efficiency, swelling index, mucoadhesion (sheep mucosae), morphology (SEM), in-vitro wash-off test, drug release profile, and stability (6 months) were evaluated. Results: Chitosan content positively correlated with microsphere size. Entrapment efficiency ranged from 51.43% to 94.15%. Chitosan-based formulations, especially MTZ-7 (Chitosan:NaCMC, 3:1), displayed the highest mucoadhesion. SEM analysis revealed rough, spherical microspheres with a continuous polymeric coat. In-vitro wash-off test demonstrated prolonged residence time for Chitosan formulations. Sustained drug release was observed throughout the study, with MTZ-7 exhibiting the most desirable release profile. Stability studies showed no significant changes in drug release for selected formulations after 6 months. Conclusions: Chitosan-based microspheres, particularly MTZ-7, demonstrated superior mucoadhesive properties, sustained and controlled drug release, and desirable stability. These findings suggest the potential of Chitosan-based microspheres as a promising oral drug delivery system for Metronidazole, potentially addressing bioavailability concerns and improving therapeutic efficacy.